2010
DOI: 10.1007/s10290-009-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Information barriers, export promotion institutions, and the extensive margin of trade

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Three studies, Polachek (), Ciuriak and Kinjo (), Volpe Martincus et al. (2010a), drop out entirely because the number of observations used for the regressions in their papers is not provided. Likewise, observations of Rose's () extensive sensitivity analyses can no longer be included when accounting for the number of observations .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies, Polachek (), Ciuriak and Kinjo (), Volpe Martincus et al. (2010a), drop out entirely because the number of observations used for the regressions in their papers is not provided. Likewise, observations of Rose's () extensive sensitivity analyses can no longer be included when accounting for the number of observations .…”
Section: Resultsmentioning
confidence: 99%
“…Later studies on the topic of export promotion and investment promotion produced positively significant effects of much smaller size (Bobonis and Shatz, 2007;van Veenstra et al, 2011). The empirical work that followed the World Bank publications had a somewhat different and wider scope and dealt with the regional effect of export promotion and embassies (Gil et al, 2008;Volpe Martincus et al, 2010a;Gil-Pareja et al, 2011), the effect of the level of development (van Veenstra et al, 2011) and the effect of export promotion on the extensive and intensive margin of trade (Segura-Cayuela and Vilarrubia, 2008;Volpe Martincus et al, 2010a, 2010bGil-Pareja et al, 2011;Volpe Martincus and Carballo, 2011). 3 Others investigated economic diplomacy by focusing on the contribution of the diplomatic service.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…G¨org et al (2008) and Bernard and Jensen (2004) found no significant impact of individual grants and subsidies on market entry. Volpe Martincus et al (2010) find that embassies and export promotion offices have a positive effect on the number of goods exported by Latin American and Caribbean countries.…”
Section: Introductionmentioning
confidence: 98%
“…4 However, these counsellors are concerned with a broad set of tasks, and trade or export promotion is only one of them. According to Martincus et al (2010), foreign missions may stimulate exports but usually these are exports of products with less severe informational impediments (products that are often already being exported) and which accordingly require fewer specific skills to deal with them. Trade counsellors are thus important in promoting exports but they are probably not the most efficient tool for diversifying the export structure, especially if SMEs are the focus of such efforts.…”
Section: Expand the Export Promotion Network Abroad And Provide A Clementioning
confidence: 99%